Anti-IL-6 Receptor Antibody Inhibits Spontaneous Pain at the Pre-onset of Experimental Autoimmune Encephalomyelitis in Mice - Serizawa, Kenichi; Tomizawa-Shinohara, Haruna; Yasuno, Hideyuki; Yogo, Kenji; Matsumoto, Yoshihiro (Frontiers in Neurology, 2019)
Chronic pain is a significant symptom in patients with autoimmune encephalomyelitis, such as multiple sclerosis and neuromyelitis optica. The most commonly used animal model of these diseases is experimental autoimmune encephalomyelitis (EAE). We previously reported that evoked pain, such as mechanical allodynia, was improved by an anti-IL-6 receptor antibody in EAE mice. However, few reports have evaluated spontaneous pain in EAE mice. Here, we assessed spontaneous pain in EAE mice by utilizing the Mouse Grimace Scale (MGS, a standardized murine facial expression-based coding system) and evaluated the influence of an anti-IL-6 receptor antibody (MR16-1). EAE was induced in female C57BL/6J mice by subcutaneous immunization with myelin oligodendrocyte glycoprotein 35-55 emulsified in adjuvant and administration of pertussis toxin. Mice were placed individually in cubicles and filmed for about 10 minutes. Ten clear head shots per mouse from the video recording were given a score of 0, 1, or 2 for each of three facial action units: orbital tightening, nose bulge, and ear position. Clinical symptoms of EAE were also scored. Measurement of 5-HT in the spinal cord and functional imaging of the periaqueductal gray (PAG) were also performed. Compared with control mice, MGS score was significantly higher in EAE mice. MR16-1 prevented this increase. Promotion of spinal 5-HT turnover and reduction of PAG activity were observed in pre-onset EAE mice, and MR16-1 tended to prevent these changes. These results suggest that spontaneous pain developed before EAE onset via an impaired descending pain inhibitory system, and that MR16-1 prevented it.